Magnitudes and capital key divergence of the Eurosystem's PSPP/PEPP purchase - update June 2023: study supported by the Brigitte Strube Foundation - Birkholz, Carlo; Heinemann, Friedrich (ZEW-Kurzexpertise, 2023)
In this report we update the quantitative analysis of the PEPP and PSPP conduct and analyze whether reinvestments are actually made in accordance to these claims. In prior versions of our report, we have detected patterns in the net purchases under PEPP and PSPP, which suggested systematic and long-run overweighting of individual countries relative to the ECB capital key. Our update assesses cumulative purchases of PEPP and PSPP over the course of the programmes, the divergence from the capital key of the final maximum PEPP and PSPP stocks in March and June 2022 respectively, and the subsequent developments since the end of net purchases until January 2023. The report closes by showing the magnitude of both programmes in each country of the Eurosystem relative to GDP and public debt.
Keywords: Graue Literatur